SOLUBILITY, SPECIATION AND DISSOLUTION MECHANISMS FOR CO2 IN MELTS ON THE NAALO2-SIO2 JOIN - PRELIMINARY RESULTS - Brooker R.A.; Kohn S.C.; Holloway J.R.; McMillan P.F.; Carroll M.R. (My University, 1999)
CO2 solubility and speciation in melts along the NaAlO2-SiO2 join from Ne (NaAlSiO4) to a model rhyolite (Ry) composition (NaAlSi6O14), have been investigated as a function of pressure (10 to 25 kb) and temperature (1450 to 1700°C). Quenched glasses have been analysed using LECO bulk carbon analysis in conjunction with Fourier transform infrared (FTIR), Raman, and 13C Magic angle spinning nuclear magnetic resonance (MAS NMR) spectroscopic measurements.In agreement with previous studies, the CO2 solubility was found to increase as a function of total pressure for the Ne, Jd (NaAlSi2O6), Ab (NaAlSi3O8), and ''Eu'' (NaAlSi4O10) compositions. The temperature dependence of the CO2 solubility was also investigated. For the Ne (15 kbar) composition, a slight increase in solubility was noted with increasing temperature, whereas a broad minimum in solubility was noted for the Jd composition (15 and 20 kbar) in the 1550 to 1650°C range. No obvious dependence of the solubility on run temperature was noted for the high silica compositions Eu to Ry at 15 kbar.Infrared (IR) and NMR spectra of the quenched glasses show that the type and relative amounts of carbon-bearing species change systematically as a function of composition. The relative and absolute abundance of carbonate (CO32-) groups increases rapidly with decreasing Si/(Na + Al) ratio, whereas the relative and absolute abundance of molecular CO2 decreases. The result is that, for a given pressure and temperature, the CO2 solubility remains approximately constant or decreases slightly with decreasing Si/(Na + Al) ratio between Ry and Jd compositions, but increases rapidly between Jd and Ne compositions, at 15 kbar and 1600°C. In the most silica-rich compositions nearly all the dissolved CO2 is in the form of molecular CO2. The IR and Raman spectra of dissolved molecular CO2 indicate some interaction with the silicate melt structure, which changes over the compositional range studied. Four different types of dissolved carbonate groups with differing degrees of distortion have been identified by NMR spectroscopy, the relative proportions changing systematically with glass composition. Two of these carbonate groups are dominant in silica-poor, carbonate-rich compositions and correlate with distinguishable features in the IR spectra. The structural changes in both the carbonate and the molecular CO2 species as a function of bulk composition along the join, result in changes in the IR extinction coefficients for these species. The degree to which the observed quenched glass species reflect the situation in the melt at run conditions are discussed.Dissolved carbon monoxide (CO) has been identified from the NMR and FTIR spectra of glasses for experiments carried out under (unintentionally) reducing conditions. The experimental results indicate that considerable caution is required in preparing nominally ''CO2 -saturated'' glasses. The absence of CO-related spectral features can be used to ensure that the experimental PCO2 is in fact equal to Ptot.